The concept and essence of land-use defense in Ukraine - Tretiak, A.; Melnichuk, A. (Land Management, Cadastre and Land Monitoring, 2018)
According to Article 77 of the "Land of Defense" of the Land Code of Ukraine, land of defense is the land granted for the deployment and ongoing activity of military units, institutions, military educational establishments, enterprises and organizations of the Armed Forces of Ukraine, other military formations established in accordance with the legislation of Ukraine [ 1]. Land of defense can only be in state ownership. Around the military and other defensive objects, if necessary, protective, security and other zones with special conditions of use are created. According to Article 2 "Legal regime of land of defense" of the Law of Ukraine "On use of land of defense" the parcels are provide to military units for accomplishment of the functions and tasks assigned to them in permanent use according requirements of the Land Code of Ukraine [2]. Features of provision the parcels of land to military units for military and other defensive objects are determined by the Cabinet of Ministers of Ukraine. This conditioned the need to carry out research on the essence of land use in Ukraine and formulate its concept.Installed that the regulation of the legal regime of most types of land of defense is absent today, and the Law of Ukraine "On use of lands of defense" doesn't respond to its name. In the subcategories of the land of the Ministry of Defense, for functional use, agricultural, forestry, nature conservation and urban land use are allocated. Unfortunately, land use is not allocated to the defense function, but part 5 of Article 20 of the Land Code of Ukraine refers precisely to the said law in terms of determining the peculiarities of the legal regime of land defense.The peculiarity of the legal regime of the land of defense is that they can be only state or communally owned  (under the objects of socio-cultural, industrial and residential purposes) property (Article 2, part 2, paragraph "c", paragraph 4 of Article 84 of the Land Code of Ukraine ) [2]. The Law of Ukraine "On use of land of defense" [1] provides that land use by the relevant subjects in the title of permanent use (Article 2 (1), but also provides (Article 4) the possibility of granting such land plots for secondary use for agricultural purposes : "military units, in coordination with local executive bodies or authorities and according to they procedure determined by the Cabinet of Ministers of Ukraine, can permit  natural persons and legal persons to grow crops, graze livestock and (harvested) hay on land provided to them for permanent use.Analysis of scientific works shows that the concept of land use should be considered in the natural, legal, economic, environmental, defense and security and other aspects.In sense defense and security terms, land-use of defense is a land mass, which consists of one, or several land plots separated on the ground, which are systematically used by military units and have a special regime to ensure the functioning of their properties, the storage of weaponry and military equipment.Consequently, land-use defense is a land mass, which consists of one, or several land plots isolated on the ground, which systematically use military formations and have a special regime for ensuring the functioning of their property objects, the preservation of weapons, military equipment and other military property. The essence of land use of defense is reflected in its characteristics as a physical object, economic, legal, social and environmental defense-security land-property relations in a market economy.Keywords. Land use of defense, land of defense, land and property relations.